Reproducibility and concordance of functional autonomy tests in older adult women: a comparative study of face-to-face and virtual assessments - Siqueira, Talles M.; Pitta, Rafael M.; Machado, Alexandre F.; Scartoni, Fabiana R.; Rica, Roberta L.; Pontes Junior, Francisco Luciano; Bullo, Valentina; Gobbo, Stefano; Bergamin, Marco; Bocalini, Danilo S. (Frontiers in Public Health, 2025)
IntroductionThe literature does not explore functional assessments carried out remotely and in older women in virtual environments.ObjectiveThis study analyzed the reproducibility and agreement in applying functional autonomy tests face to face (FF) and virtually (V).MethodsA single evaluator carried out two evaluations. The following tests were performed: walking 10 m, rising from the sitting position (RSP), rising from the ventral decubitus position (RVDP), and sitting and rising from a chair and walking around the house (SRCW).ResultsNo significant changes were identified between V and FF (p > 0.05 for all). No significant changes were identified between tests considering FF and V conditions (p > 0.05 for all). The highest value for the intraclass correlation coefficient was <0.0001 for the SRCW (CL, r = 0.98 CI95%: 0.969–0.990 and ICC, r = 0.99 CI95%: 0.984–0.995), and the lowest was <0.0001 for the RSP (CL, r = 0.91 CI95%: 0.853–0.954 and ICC, r = 0.95 CI95%: 0.921–0.976). Regarding agreement between tests, a variation was found between the lowest value of 0.07 ± 0.74 BIAS for the RVDP and the highest value of 0.32 ± 1.89 BIAS for the SRCW.ConclusionThe tests used in the present study showed good reproducibility and agreement in older people when carried out face to face and virtually.